Spatial Analysis of Terrestrial Nuclear Radiation Dose Rate in the Eastern Region of Peling Island Using Type 6 Pocket Geiger Detector - ANGGRAINI DAUD; Asri Arbie; Muh. Fachrul Latief; Syafril Agustion Tomayahu; Siti Sarah Dayanun; Awaludin Ismuhu (Departement of Physics Faculty of Mathematics and Natural Sciences, and Institute of Research and Community Services Udayana University, Kampus Bukit Jimbaran Badung Bali, 2026)
Terrestrial nuclear radiation is natural radiation originating from the decay of radionuclides in rocks and soil, with a distribution influenced by the geological and geomorphological conditions of the region. Peling Island, Banggai Islands Regency, is dominated by karst areas that have the potential to influence the distribution of terrestrial nuclear radiation, but spatial information regarding radiation in this region is still limited. This study aims to analyze the spatial distribution of terrestrial nuclear radiation dose rates in the eastern region of Peling Island. Measurements were carried out at 144 sample points systematically distributed using an observation grid measuring 1500 m × 1500 m. At each point, a Pocket Geiger Type 6 detector was placed at a height of ±1 m above the ground surface and connected to a smartphone via the Pocket Geiger Type 6 application. Data were recorded every 2 minutes, and stored in CSV and KML formats. The data were then processed using two software, namely, ArcgGIS with the IDW method and Python for spatial classification and analysis. The results showed a uniform distribution of radiation dose rates without any spikes or extreme differences between measurement areas, with a range of ≤0.02 to 0.14 µSv/h and an average of 0.0504 µSv/h. The annual effective dose was recorded at 0.0883 mSv/y. This value is still below the effective dose limit for the general public of 1 mSv/y.